High Thermal Stability Silica Nanofluids For EOR in Sandstone Reservoir - Subagio, Agus; Rowi, Khasan; Taufiq, Heydar Ruffa; Azis, Muhammad Mufti; Prasetiyo, Bayu Dedi; Sitompul, Victor; Paryoto, Sumadi; Winata, Denie Tirta; Diharja, Tino; Yutaka, Michael Arya; Syarifudin, Abimanyu Putra; Firmansyah, Wahyu; Koestono, Hary; Ngadiwiyana (Scientific Contributions Oil and Gas, 2026)
The development of silica nanofluids for enhanced oil recovery (EOR) has gained significant attention. However,  their application is limited bypoor stability under high temperature, and high salinity conditions. Our previous studies demonstrated that using the anionic surfactant alpha olefin sulfonate (AOS) combined with the co surfactant disodium laurent sulfosuccinate (DLS) at consentrations of 0.3% AOS and 0.3% DLS significantly enhanced thermal stabilility, reduced IFT, decreased wettability, and increased incremental oil recovery. This study reports a one step synthesis method for preparing silica nanofluids using hydrophilic colloidal nano silica (CNS) stabilized with the AOS and DLS at surfactant concentrations above 0.3%. Nanofluids were formulated with formation water from a reservoir in Sumatra, Indonesia. We systematically evaluated the effects of AOS-DLS concentrations on the thermal stability, turbidity, interfacial tension (IFT), wettability, filtration test, and core flooding performance. The optimized formulation of stable silica nanofluids for EOR applications under reservoir relevant conditions was also systematically evaluated. The silica nanofluid (0.3% AOS + 0.3% DLS) exhibited more than 3 months of stability at 60 °C. It also had a low contact angle of 13.88 ͦ and a reduced IFT of 6.3x10-1 mN/m. The filtration ratio was 1.2. Spontaneous imbibition resulted in a recovery factor (RF) of 59%. Core flooding analysis yielded an incremental RF of 12.9% of the OOIP. These results demonstrate the synergistic role of silica nanoparticles and surfactants in improving nanofluid stability, reducing IFT, and enhancing oil recovery. This supports their potential application in chemical flooding for sandstone reservoirs.